Influence of food allergy on atopic dermatitis in infants and children under 10 years: a study in Iran - Shiravi Khouzani, Mohammad; K., Krishnaveni (International Journal of Research in Medical Sciences, 2023)
Background: Based on the data collected from 220 cases of children and infants in Iran, aged under 2 months to 10 years, over a period of 6 months (2021-2022),there is evidence of a relationship between food consumption and the occurrence of Atopic dermatitis (AD). Methods: It is an institution based Case-Control study. Analytical observational studies. Results: It was found that 28.6% had IgE levels ranging between 150-250 u/ml. The majority of these patients consumed breast milk (n=83) or milk powders (n=75).In terms of the location of AD symptoms, 31.3% of the cases involved the chin and face. Conclusions: The duration of treatment for these patients ranged from 6 to 8 months. Gastrointestinal problems and asthma allergies were also observed among the patients, which could be attributed to an increase in cytokines and pro-inflammatory factors. These findings highlight the influence of food consumption on the development of AD in Iranian children and infants. It suggests that certain foods, including breast milk and milk powders, may be associated with the occurrence of AD in this population.